Armadillogorgia albertoi sp. nov.: a new primnoid from the Argentinean deep sea - Cerino, Nadia; Lauretta, Daniel (Zootaxa, 2013)
Eleven specimens of a new species of primnoid from the Argentinean deep sea are here presented. Armadillogorgia albertoi sp. nov. differs from A. cyathella Bayer, 1980 in colony and polyp morphology, abaxial sclerite number and shape. It is the second species of the hitherto monospecific genus, and the northernmost record of the genus.